Nitrogen and Phosphorus Dual-Doped Multilayer Graphene as Universal Anode for Full Carbon-Based Lithium and Potassium Ion Capacitors - Luan, Yuting; Hu, Rong; Fang, Yongzheng; Zhu, Kai; Cheng, Kui; Yan, Jun; Ye, Ke; Wang, Guiling; Cao, Dianxue (Nano-Micro Letters, 2019)
Lithium/potassium ion capacitors (LICs/PICs) have been proposed to bridge the performance gap between high-energy batteries and high-power capacitors. However, their development is hindered by the choice, electrochemical performance, and preparation technique of the battery-type anode materials. Herein, a nitrogen and phosphorus dual-doped multilayer graphene (NPG) material is designed and synthesized through an arc discharge process, using low-cost graphite and solid nitrogen and phosphorus sources. When employed as the anode material, NPG exhibits high capacity, remarkable rate capability, and stable cycling performance in both lithium and potassium ion batteries. This excellent electrochemical performance is ascribed to the synergistic effect of nitrogen and phosphorus doping, which enhances the electrochemical conductivity, provides a higher number of ion storage sites, and leads to increased interlayer spacing. Full carbon-based NPG‖LiPF6‖active carbon (AC) LICs and NPG‖KPF6‖AC PICs are assembled and show excellent electrochemical performance, with competitive energy and power densities. This work provides a route for the large-scale production of dual-doped graphene as a universal anode material for high-performance alkali ion batteries and capacitors. Highlights: 1 Nitrogen and phosphorus dual-doped multilayer graphene (NPG) was prepared by arc discharge process. 2 NPG exhibits good rate capability and stable cycling performance in both lithium and potassium ion batteries. 3 Full carbon-based lithium/potassium ion capacitors are assembled and show excellent electrochemical performance.